P084 Poroinflammatory environment in RA and OA strongly influences adipose tissue activity. (21st February 2018) - Plebanczyk, M; Radzikowska, A; Musialowicz, U; Janicka, I; Kornatka, A; Maslinski, W; Kontny, E
Abstract : Introduction: Rheumatoid arthritis (RA) and osteoarthritis (OA) are inflammatory diseases leading to joint destruction and disability. Apart from joint inflammation they are characterised by high-grade (RA) or low-grade (OA) systemic inflammation. Thus, it is possible that proinflammatory environment affect not only articular (AAT), but also subcutaneous adipose tissue (ScAT) activity. Objectives: The aim of present work was to compare reactivity of AAT and ScAT from RA and OA patients to proinflammatory stimulus. Methods: AAT and ScAT explants, obtained from OA (n=44) and RA (n=43) patients during knee joint replacement surgery, were cultured (100 mg/ml) for 24 hours in medium (DMEM) alone or in the presence of proinflammatory IL-1β (1 ng/ml), known to be overproduced in inflamed joint. Concentrations of cytokines (proinflammatory IL-6 and TNF, anti-inflammatory IL-1Ra, IL-10, TGFβ), chemokines (CCL2, CCL5) and metalloproteinase MMP-3 were measured in culture supernatants by ELISA. OA patients were treated with non-steroidal anti-inflammatory drugs while RA patients were given disease modifying drugs and/or glucocorticosteroids. Data were analysed as stimulation to control ratio (IS, index of stimulation) using Mann-Whitney U test and are expressed as median. Results: In OA the levels of secreted factors were usually significantly higher in AAT, but ScAT was characterised by significantly higher increase of IL-6 (IS=16.4), TGFβ (IS=2.0), CCL2 (IS=1.8), and MMP-3 (IS=9.9) production than AAT (IS=70.3; 1.3; 1.3; 2.4 respectively). The up-regulation of other cytokines was similar in both tissues. By contrast, in AAT and ScAT from RA patients IL-1b-triggered increase of all tested factors secretion was similar. Moreover, upon IL-1b treatment the up-regulation of IL-6 (IS=13188) and MMP-3 (IS=9, 1) in AAT of RA patients as well as of CCL2 from rheumatoid AAT (IS=3.2) and ScAT (IS=3.7) was significantly higher than in OA tissues (IS=70.3; 2.4; 1.3; 1.8 respectively). References: We report that in OA ScAT, exposed in vivo to low-grade inflammation, retains higher reactivity to proinflammatory stimulus than AAT located in chronic high-grade inflammation. In RA, however, reactivity of both adipose tissue is rather similar but in the case of secretion of some factors (CCL2 and/or IL-6, MMP-3) higher than in OA, reflecting more destructive character of this disease. Acknowledgements: This work was funded by the National Science Centre (grant number 2012/N/NZ5/00074). Disclosure of interest: None declared